A 'Design for Energy Minimization' approach to reduce energy consumption during the manufacturing phase. (15th August 2016) - Seow, Yingying; Goffin, Nicholas; Rahimifard, Shahin; Woolley, Elliot
Abstract: The combustion of fossil fuels for energy generation has contributed considerably to the effects of climate change. In order to reduce fossil fuel consumption, designers are increasingly seeking to reduce the energy consumption of products over their life cycle. To achieve a significant reduction in energy consumption, it is essential that energy considerations are incorporated within the design phase of a product, since the majority a product's environmental impact is determined during this phase. This work proposes a new 'Design for Energy Minimization' (DfEM) approach, which is intended to provide increased transparency with respect to the energy consumed during manufacture in order to help inform design decisions. An energy simulation model based on this approach is then presented to aid designers during the design phase. The application of this novel design tool is demonstrated in two cases: That of a simple product (designed by a single Original Equipment Manufacturer (OEM) through a centralized approach); and a complex product (designed by a number of designers within a supply chain using a distributed approach). The subsequent benefits to energy minimization are then discussed and conclusions drawn. Highlights: A novel "Design for Energy Minimization" (DfEM) methodology is presented. The tools used for the methodology at each phase of the design process are shown. Its application in the design of a simple product is demonstrated. Its application with a complex product with multiple supply chains is demonstrated.